Currículo e Exame Nacional do Ensino Médio: rupturas e permanências na conformação dos saberes históricos escolares - Bergamin, Fabíola Matte (2013)
This work intended to accomplish a comparison between the competencies and skills for History as school subject existent in the National Evaluation of the Secondary Level ENEM and the competencies and skills proposed by the National Curricula Standards (PCNEM and PCN+). The aim was to observe the changes and the endurances during 1998 to 2011, regarding the conception of History present in the exams, as well as analyze the National Evaluation of the Secondary Level ENEM´s reformulations in order to verify if it can considered an instrument that reflects the implementation of the National Curricula Standards (PCNEM and PCN+). Finally, there´s the inquiring if ENEM´s reformulations are related to the Ministry of Education and the federal universities´ demands. Official documents, particularly the PCNEM and PCN+, and the questions from ENEM were the main sources investigated. Concepts of curriculum developed by Goodson (2012), Gimeno Sacristán (1998) e Apple (1982), and concepts of school subject and humanities elaborated by Chervel (1999) were used to base the documental analysis